ALLELOPATHICAL ACTIVITY ASSESSMENT AS THE IMPORTANT STAGE OF PHYTOREMEDIATION TECHNOLOGY DEVELOPMENT - Shtyka, Olga; Bilyk, Tetyana; Andrushchenko, Olena (Proceedings of National Aviation University, 2015)
Phytoremediation is acknowledged as the perspective technology of soil decontamination and recovery. Nevertheless, there are certain factors that are supposed to influence this process, decreasing its effectiveness. The introduction of phytoremediation plants as the non-indigenous species into a phytocenosis of contaminated area may initiate the activation of an allelopathic activity of the present species. Allelopathic activity is commonly defined as a process of secretion of the secondary metabolites in a form of volatile compounds, exudates that inhibit development of other plants. Thus, this research work focuses on the assessment of an allelopathic activity of the indigenous species and its influence on selected phytoremediation plants. Bioassay and germination test have been conducted to measure the effects of water-soluble extracts of Amaranthus retroflexus L., Cirsium arvense L., Barbarea vulgaris R. Br. and Artemisia absinthium L. on the introduced species used in phytoremediation.